Analysis of Electromagnetic Emissions for Data Protection - Hapichenko, A. M.; Zabolotnyi, V. I. (ХНУРЕ, 2025)
This paper analyzes stray electromagnetic emissions from the video path of computing devices to assess information leakage risks. A mathematical model using the transfer function evaluates electric and magnetic fields across wide frequency and distance ranges. The results aid in developing effective information protection systems, offering solutions to enhance data security.
Keywords: stray electromagnetic emissions; computing devices; transfer function; information security; video path